Analisis Dampak Kurangnya Fasilitas Service Road terhadap Pergerakan Penumpang di Apron Bandar Udara Internasional Husein Sastranegara Bandung - Augusta, M. Yanuar; Purnama, Yunus (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Service Road markings are very important and mandatory markings for every Domestic and International Airport which have an important role in supporting the safety of passenger movements and regular flight at Husein Sastranegara International Airport Bandung. The aim of this research isTo find out what causes the absence inApron Husein Sastranegara International Airport Bandung, to find out what the impact of its absence isService Road on the movement of passengers inApron Bandung Husein Sastranegara International Airport, and to find out the efforts of the AMC unit against their absenceService Road OfApron Bandung Husein Sastranegara International Airport. In this study, the research used qualitative methods with data collection techniques used were observation, interviews, and documentation. The research was carried out from 1 August 2022 to 30 September 2022 and continued with observation activities for 4 days from 24 February 2023 to 27 February 2023. Observations made in this study were observations and reviews at the Apron Movement Control Unit at Husein International Airport Bandaung Literature. The informants or respondents in this study were workers at the Apron Movement Control Unit at Husein Sasatranegara International Airport, Bandung. Documentation in this study is documentation of activities that occur in the Apron area or the movement of aircraft, passengers and workers. The results of the study show that Bandung Husein Sastranegara International Airport does not have a Service Road due to limited land which of course this can cause an impact or risk of aviation traffic accidents at Bandung Husein Sastranegara International Airport. Efforts made by the AMC Unit to overcome these impacts are by increasing the performance of the AMC Unit at Bandung's Husein Sastranegara International Airport. Keywords: Passenger Movement, Service Road, Bandung Husein Sastranegara International Airport.